Keabsahan Hukum Jual Beli Emas Tanpa Nota Pembelian Pada Pelaku Usaha Emas Di Pasar Swadaya Jembrana - Muhammad Nuha Maulana Pasya; Reni Anggriani (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2023)
Inside Pasar Swadaya Jembrana have at least 23 gold shops. In practice, the process of gold transactions does not always run smoothly. The making of gold have an obstacle in the gold sale and purchase agreements, gold's proprietor sometimes does not include purchase notes. Then brings discourse to legal issues, namely looking at the validity of the sale and purchase agreement and seeing whether the price set imposed on the store owner is by the process and mechanism that is not contrary to the law. This Research uses normative-empirical methods and qualitative with a constructivist paradigm. Found the validity of a gold jewellery sale and purchase agreement without a purchase note can be notarized as valid if it refers to Article 1320 KUHPer by not violating the provisions of that article. The determination and cut in the price of gold jewellery inscribed by the latter has the consequence that increasing the number of gold rebates to be sold, is based upon defaults made by the party (gold owner). The pricing is not done haphazardly, but with a negotiation process, until an agreement is reached, the calculation necessary is inseparable from the "package" that has been carried out in the world of gold jewellery transactions.